High power, extended temperature range, highly resistant to abuse, overcharge and discharge, rechargeable battery cells and packs
By using polycrystalline cathode and high redox potential anode electrochemically active materials in lithium-ion batteries, combined with aluminum current collector and polymer separator, the safety and performance problems of lithium-ion batteries in mechanical abuse, low and high temperatures are solved. A battery design with high power output and long cycle life is achieved.
Patent Information
- Application Number
- CN202080042449.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-12
- Filing Date
- 2020-04-10
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2040-04-10
AI Technical Summary
Existing lithium-ion batteries have safety problems under conditions such as mechanical abuse, low-temperature charging, overdischarge and overcharge, and their performance in long-term storage and transportation makes it difficult to achieve high power output and long cycle life.
Using a battery design consisting of polycrystalline cathode electrochemically active material and anode electrochemically active material with high redox potential, combined with aluminum current collector and polymer separator, ensure that the area ratio of the anode to cathode is less than or equal to 1, and the electrolyte is in A lithium salt solution with high ion conductivity is used.
Achieve high-performance output of lithium-ion batteries under extreme mechanical abuse, low temperatures and high temperatures, can safely discharge to 0V, withstand overcharge and voltage reversal, extend the battery cycle life and storage time, and provide improved safety and high power capability.
Smart Images

Figure CN113966554B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application is a continuation-in-part of U.S. Patent Application No. 16 / 383,079, filed on April 12, 2019, and depends upon and claims the benefit of International Application No. PCT / US2019 / 027284, filed on April 12, 2019, the entire contents of each of which are incorporated herein by reference.
[0003] field
[0004] The present disclosure relates to lithium ion secondary batteries and their uses.
[0005] background
[0006] Lithium-ion batteries are the primary power source for many portable electronic devices for a variety of reasons, including the high energy density, high specific energy, and long cycle life associated with the technology. However, commercially available lithium-ion batteries have safety issues, especially when they are subject to mechanical abuse. They cannot be quickly charged or charged at very low temperatures, and typically have poor performance at low temperatures. They are capable of violent safety failures, especially when they are subject to mechanical abuse such that they form internal short circuits. They are sensitive to overdischarge and overcharge, and can exhibit undesirable performance losses and possible unsafe events if a battery or a cell of a battery is overcharged or overdischarged.
[0007] Long-term storage or transportation of lithium-ion battery packs is problematic due to their sensitivity to over-discharge. Due to the limited rate of self-discharge, long-term storage of battery packs causes the battery pack voltage to slowly approach 0V. In a discharged battery pack composed of many cells, inherent or introduced inter-cell capacity imbalances drive a small group of cells into a voltage reversal or over-discharge state. In most common lithium-ion battery pack cell designs, these voltage conditions trigger and accelerate harmful reactions that irreversibly damage cell performance.
[0008] While not wishing to be bound by theory, it is understood that the over-discharge sensitivity of existing lithium-ion batteries stems from the combination of the graphite anode material and the copper current collector material used. Copper is used because it does not readily electrochemically alloy with lithium at the redox potential of graphite and has high conductivity. However, if the anode is driven to a high potential (~3 V vs. Li / Li +) - This can occur when the battery is over-discharged, and the copper can be oxidized. The oxidized copper is understood to be redeposited in the form of fibers, which can limit lifetime and can cause internal short circuits if the battery is subsequently recharged. In addition, the passivation films formed at the interface of the electrolyte and the electrode material that mitigate parasitic degradation reactions can decompose in oxidative over-discharge conditions, especially at elevated temperatures. When the battery begins cycling again, these passivation films must be reformed, thereby consuming additional lithium and reducing the overall capacity of the battery.
[0009] One way to improve the over-discharge stability of graphite anodes is to replace the copper current collector material with stainless steel or titanium, which are more resistant to dissolution at high potentials. However, both stainless steel and titanium have higher electronic resistivity than copper, which requires a battery design with a thicker current collector and thus ultimately limits the battery power capacity. Another way to improve the over-discharge stability of graphite anodes is to pre-lithiate the anode, which reduces the anode potential in the over-discharge state to below the copper dissolution potential. However, this method can cause the cathode potential to reach a lower potential in over-discharge corresponding to over-lithiation that may cause degradation, and may also lead to an increased risk of Li plating on the anode at the peak of charge.
[0010] To avoid these and other safety issues, cells in currently available lithium-ion battery packs are electronically monitored and their state of charge is controlled, a task that can be performed using a battery management circuit (BMC). In addition to protecting lithium-ion cells from excessive discharge and from degradation mechanisms such as copper dissolution, battery management circuits can also provide overcharge protection. The cell monitoring and charge state control used in existing lithium-ion battery packs generally exceeds that used in other rechargeable battery pack technologies, such as lead-acid or nickel metal hydride battery packs, where battery management circuits can be omitted in many applications.
[0011] Batteries constructed with graphite anodes are most often designed to have a negative electrode / positive electrode capacity ratio 'n / p' greater than 1 to avoid lithium precipitation at the anode during charging. Since the graphite intercalation potential is only ∼0.1 V higher than the precipitation potential of lithium metal, during normal mode battery charging, lithium metal deposition reactions may occur at the anode rather than the preferred lithium intercalation reaction into graphite, which poses a safety risk and the risk of catastrophic battery failure. A common preventative measure to prevent Li metal precipitation is to design the battery with n / p>1, typically between 1.1 and 1.3, which ensures that the lithium inventory in the battery is less than the capacity defined by the number of intercalation sites in the graphite anode crystal structure. This battery configuration then defines the fully charged state as a fully deintercalated cathode and a partially intercalated anode. For such a battery design, careful monitoring from the BMC is required to avoid an upper voltage threshold associated with accelerated cathode degradation. On the other hand, if the battery is designed to have n / p<1, then as the battery voltage increases during charging, at some point, the lithium metal precipitation reaction becomes the thermodynamically preferred electrochemical reaction at the anode after all graphite intercalation sites have been occupied by Li. For such a cell design, careful monitoring from the BMC is required to avoid an upper voltage threshold, where Li precipitation occurs. Accordingly, the risk of Li precipitation causing catastrophic failure is expected to be too high at n / p ratios less than 1.
[0012] Batteries constructed with graphite anodes suffer from poor charging at low temperatures. Due to the slow kinetics of increasing cell polarization at low operating temperatures, the anode potential easily drops below the Li precipitation potential, which is only 0.1 V, thereby accelerating cell degradation and even inducing catastrophic failure. As such, batteries constructed with such designs have severe limitations on charging power capacity at low temperatures. If an external heating device is not used, low temperature charging may be completely impossible and careful monitoring from the BMC is required to avoid high rate charging at low temperatures.
[0013] During storage and operation of lithium-ion batteries, parasitic interactions between battery components can lead to the generation of gas, resulting in increased pressure and reduced battery performance. Gassing is exacerbated at elevated temperatures and typically when the battery is driven to the electrolyte oxidation potential. In prismatic and pouch formats, gas accumulation within the battery can lead to mechanical deformation of the battery housing and can damage the connections between the cells in the battery pack, thereby increasing the risk of catastrophic failure. In addition, excessive pressure can damage the cell seal to cause toxic gas discharge and premature battery failure.
[0014] Lead acid (Pb acid) batteries are currently used in vehicle ignition and start-stop battery applications, such as "start-light-ignition" (SLI) applications, because robust batteries are needed to deliver power over a wide temperature range. However, as the hybridization of vehicles increases, additional energy-consuming components are powered by lead acid batteries (i.e., air conditioning, regenerative braking, seat heaters). As a result, lead acid batteries are forced out of their ideal operating window, into a greater state of charge (SOC) and undergo a greater number of cycles, resulting in reduced performance and more frequent replacement.
[0015] Therefore, there remains a need for battery technology that provides some of the desirable properties of lithium-ion batteries, such as long cycle life, and the properties currently provided by lead-acid SLI batteries, such as high power, rapid recharge, and low temperature performance. In addition, technology that provides improved safety, including safely withstanding extreme mechanical abuse and safely operating to, for example, 0V without external circuitry for over-discharge protection, is highly desirable.
[0016] Overview
[0017] The following summary is provided to facilitate understanding of some of the innovative features unique to the present disclosure and is not intended as a complete description. A full appreciation of the various aspects of the present disclosure can be gained by taking the entire specification, claims, drawings, and abstract as a whole.
[0018] Disclosed are rechargeable lithium-ion cells and battery packs that are robust, very safe, exhibit high power delivery and reception capabilities, have long cycle life, excellent performance at both high and low temperatures, are very resistant to mechanical abuse, and can be stored for long periods of time.
[0019] The electrochemical cells of the present disclosure are found to surprisingly withstand extreme mechanical abuse and continue to function as electrochemical cells, i.e., support charging and discharging, even after such mechanical abuse. Some aspects of the cells as provided herein are also capable of being discharged and charged at extremely low temperatures, stored for long periods of time at 0 volts without damage and withstand overcharging without damaging the cell, or a combination thereof.
[0020] A battery as provided herein includes a cathode formed of a polycrystalline cathode electrochemically active material having the formula Li 1+x MO 2+y Define or include formula Li 1+x MO 2+y, wherein -0.9≤x≤0.3, -0.3≤y≤0.3, and wherein M comprises 80 atomic % or more Ni relative to total M. The cathode electrochemically active material is further characterized by a non-uniform distribution of Co on, within or throughout the particles. The active cathode material can enhance rate performance and battery operating life compared to prior art lithium ion cathode materials. The active cathode material can be designed to reduce transition metal dissolution that is known to exacerbate parasitic decomposition and gassing reactions at the anode.
[0021] The battery provided herein comprises a Li / Li bond having a voltage of greater than 400 mV vs (vs) + The redox potential of the anode material is defined by the electrochemical activity of the anode material. + Operating at least 400 mV above the redox potential greatly reduces the tendency of the battery to undergo lithium precipitation during charging, because the electrode must be polarized at least 400 mV to reach the thermodynamic potential for precipitation. The battery provided herein can achieve high power output even at low temperatures because the polarization caused by the poor kinetics at lower temperatures can be overcome without the risk of lithium precipitation. + Batteries with anodes with redox potentials of 2.5 to 4.5 W cannot tolerate large polarizations caused by poor kinetics, as these polarizations will cause lithium precipitation at the anode.
[0022] The cells can be in any configuration, such as cylindrical or pouch cells.
[0023] The anode and cathode are in ionic contact with and separated by a separator. The separator may include or may be a polymer separator. In some aspects, the separator may include a polyolefin. In some aspects, the separator may further include a ceramic coated on one or more separator surfaces, or optionally on one or more separator surfaces, embedded in a polymer. The ceramic may be a ceramic such as a ceramic oxide. In some aspects, the separator is or includes aluminum oxide.
[0024] The battery of the present disclosure has the ability to be configured in an anode limited manner. As such, the area ratio of the anode to the cathode is optionally less than or equal to 1. Additionally or alternatively, the capacity ratio of the anode to the cathode electrochemically active material is equal to or less than 1.
[0025] An electrolyte may be included, wherein the electrolyte may include a solvent and a salt. Optionally, the solvent is a carbonate solvent or a combination of one or more carbonate solvents with other suitable materials. The salt is optionally a lithium salt, optionally a LiPF6 salt, in a mixture of propylene carbonate, ethyl methyl carbonate and methyl butyrate.
[0026] The anode and cathode may include a binder intermixed with the anode active material and the cathode active material. The binder is optionally a polymer binder, optionally including or consisting of polyvinylidene fluoride (PVDF).
[0027] Attached photos
[0028] Electrochemical cells according to the present disclosure are described more fully below with reference to the accompanying drawings, in which various aspects are shown. However, the present invention may be embodied in many different forms and should not be construed as limited to the aspects described herein. Rather, these aspects are provided to make this disclosure thorough and complete and to fully convey the scope of the invention to those skilled in the art. Like reference numerals refer to like elements throughout. The above and other aspects, advantages and features of the present disclosure will become more apparent by describing exemplary aspects thereof in more detail with reference to the accompanying drawings, in which:
[0029] Figure 1 is a schematic diagram of one aspect of a lithium-ion battery, with details of the electrode stack on the right;
[0030] Figure 2 Graphing voltage (volts, V) vs. capacity (ampere-hours, Ah) for various rates of charge and discharge at room temperature for a battery according to some aspects as provided herein;
[0031] Figure 3 Graphing voltage (volts, V) vs. capacity (ampere-hours, Ah) for various rates of charge and discharge at -50°C for a battery according to some aspects as provided herein;
[0032] Figure 4 Graphing battery discharge capacity (mAh) vs. cycle number for high rate cycling at 45° C. for 2 batteries according to some aspects as provided herein;
[0033] Figure 5 Graphing voltage (volts, V) vs. capacity (mAh) for charging (A) and discharging (B) at various constant powers at room temperature for a battery according to some aspects as provided herein;
[0034] Figure 6 Graphing cell voltage (volts, V) and electrode V vs. Li reference (volts, V) vs. elapsed time (minutes) for voltage reversal at room temperature for a cell according to some aspects provided herein;
[0035] Figure 7 Graphing voltage (volts) vs. capacity (Ah) of discharge of a battery at room temperature according to some aspects as provided herein before and after its inversion;
[0036] Figure 8Graphing voltage (volts) vs. discharge capacity (mAh) of a battery according to some aspects provided herein at -18°C for repeated high rate pulse discharge before and after its inversion;
[0037] Fig. 9 Graphing cell voltage (volts, V) and electrode V vs. Li reference (volts, V) vs. elapsed time (minutes) for 10% overcharge at room temperature for a cell according to some aspects provided herein;
[0038] Fig.10 Graphing voltage (volts) vs. capacity (Ah) of discharge of a battery at room temperature according to some aspects as provided herein before and after overcharging thereof;
[0039] Fig.11 Graphing voltage (volts) vs. discharge capacity (mAh) of a battery according to some aspects provided herein at -18°C before and after overcharging thereof;
[0040] Fig.12 Graphing voltage (volts, V) vs. capacity (ampere-hours, Ah) at various rates of charge and discharge at room temperature for a battery according to aspects provided herein before and after it has been subjected to a large number of cycles and subsequently stored at 0V;
[0041] Fig.13 Graphing voltage (volts, V) and temperature (° C.) vs. elapsed time (sec.) during blunt nail penetration abuse testing of a battery according to some aspects as provided herein;
[0042] Fig.14 Graphing voltage (volts, V) vs. capacity (ampere-hours, Ah) of a battery according to some aspects provided herein at room temperature before and after it has been subjected to round bar crush testing;
[0043] Fig.15 are photographs showing the integrity and continued operation of a battery after multiple extreme mechanical abuses according to some aspects as provided herein;
[0044] Fig.16 Graphing voltage (volts, V) vs. capacity (ampere-hours, Ah) of a battery at room temperature according to some aspects provided herein before and after it has been subjected to multiple extreme mechanical abuses;
[0045] Fig.17Graphing the battery discharge capacity (Ah) vs. cycle number of successive cycles of a battery according to some aspects provided herein after it has been subjected to multiple extreme mechanical abuses; and
[0046] Fig.18 Graphs voltage (volts, V) vs. capacity (ampere-hours, Ah) of a battery according to aspects provided herein at room temperature before and after it has been subjected to multiple extreme mechanical abuses, 1000 cycles, and storage at 0V for 33 months.
[0047] Details
[0048] Surprisingly, it has been found that the lithium-ion battery of the present disclosure can safely withstand extreme mechanical abuse, such as nail penetration and round bar crushing, and comprises: a positive electrode comprising a polycrystalline cathode electrochemically active material optionally having an inhomogeneous distribution of cobalt, aluminum, or both, and a positive electrode comprising a cathode electrochemically active material having a voltage at or above 400 mV vs Li / Li + The negative electrode is a negative electrode of a negative electrochemically active material characterized by an electrochemical redox potential of , the negative electrode material being coated on an aluminum current collector. Unexpectedly, the battery of the present disclosure continues to work electrochemically without significant performance loss after such abuse. In addition, the battery of the present disclosure has the unique ability to accept extremely high charge rates, have excellent recovery rates after long-term storage in a deep discharge state (e.g., 0V), and be charged at high rates (e.g., 1C) at extremely cold temperatures, such as -40°C or lower. Therefore, the battery of the present disclosure solves many problems of other battery systems and technologies by providing a particularly robust and safe battery system that can be used for many battery types, including soft pack batteries, and for many different applications.
[0049] As used herein, "absorption" may refer to: intercalation or insertion or conversion alloying reaction of lithium with an active material. Absorption may be referred to herein as "lithiation".
[0050] As used herein, "desorption" may refer to: de-intercalation or de-insertion of lithium from an active material or a conversion dealloying reaction. Desorption may be referred to herein as "delithiation".
[0051] As used herein, in the field of lithium-ion batteries, "cathode" refers to the positive electrode, and "anode" refers to the negative electrode.
[0052] As used herein, an "active material" is a material that participates in the electrochemical charge / discharge reaction of an electrochemical cell (eg, by absorbing or desorbing lithium).
[0053] The lithium-ion batteries disclosed herein can be safely discharged to 0V without affecting their performance. These lithium-ion batteries can also safely tolerate high levels of overcharge and voltage reversal, the latter property enabling battery packs made of these batteries in series to also be discharged to 0V without addressing a single battery. Since the lithium-ion batteries and battery packs disclosed herein can be discharged to 0V, many benefits are obtained. For example, the lithium-ion batteries and battery packs disclosed herein can be stored and / or transported in a discharged state to provide improved safety. Since the batteries are highly tolerant to overcharge and overdischarge, battery packs made from them can tolerate loss or failure of battery management while maintaining performance and life at safe and useful levels. The lithium-ion batteries as provided herein can also be charged extremely quickly and at low temperatures without affecting their safety, performance or life, making them very suitable for applications such as electrical load levelling and start-stop vehicle battery packs. In addition, such lithium-ion batteries have excellent stability at high temperatures and excellent performance at extremely low temperatures.
[0054] Without being bound by a particular theory, it is believed that the choice of anode structure and material greatly contributes to providing several unique characteristics of electrochemical cells as provided herein. One strategy for providing a lithium ion battery pack that can be discharged to 0 volts or stored in a discharged state while avoiding degradation of at least the commonly used copper current collector is to use a less oxidizable metal, such as titanium or stainless steel, in the current collector. However, titanium and stainless steel are not as conductive as copper. For example, the electrical conductivity of copper is more than 20 times that of titanium. Therefore, the rate performance of a battery using titanium or stainless steel instead of copper is less than when copper is used. Accordingly, for some applications, the rate performance provided by a battery using a titanium or stainless steel current collector is insufficient. Although the use of a titanium or stainless steel current collector can provide improved over-discharge performance, the use of titanium or stainless steel may make the battery unsuitable for applications requiring high power capabilities.
[0055] As provided herein, by providing including or consisting entirely of less than 0.5 volts vs. Li / Li + , for example 0.1 volt to less than 0.5 volt vs. Li / Li + The present invention provides an electrochemical cell with a negative electrode current collector made of a metal such as aluminum that can electrochemically react with lithium at a potential equal to or greater than 400 mV vs. Li / Li. + The negative electrode electrochemically active material defined by the redox potential of the aluminum alloy is used in combination because the electrochemical potential of the negative electrode electrochemically active material is greater than the potential of the aluminum alloy relative to lithium. As a non-limiting example, LTO according to some aspects provided herein has a 1.55 volt vs. Li / Li +The electrochemical redox potential is greater than the potential of aluminum alloy relative to lithium (0.4V vs.Li / Li + ). Thus, if LTO with an electrochemical redox potential of 1.55 volts vs. lithium is used (as an example), challenges associated with copper, such as copper dissolution, can be avoided by using aluminum for the current collector of the negative electrode. In addition, and while not wishing to be bound by theory, it is understood that due to its high potential relative to lithium, it is believed that no solid electrolyte interface (SEI), which is understood to include electrolyte reduction products, is formed on the negative electrode electrochemically active material as used herein. These properties, combined with the ability to safely discharge to 0V, result in a lithium-ion battery with unexpectedly improved safety and stability.
[0056] In addition, since the negative electrode including the negative electrode electrochemically active material having an electrochemical redox potential of 400 mV vs. lithium has highly reversible Li insertion, which has facile electrochemical kinetics, and the current collector including aluminum is relatively conductive, a lithium-ion battery including such a negative electrode can provide high rate performance and excellent lifespan for both charging and discharging.
[0057] Thus, an electrochemical cell as provided herein comprises a cell having a voltage of 400 mV or more vs Li / Li + The cathode is a cathode of a negative electrode electrochemically active material having a redox potential of , wherein the negative electrode electrochemically active material is coated on an aluminum current collector. In some aspects, the positive electrode also includes a polycrystalline cathode electrochemically active material coated on an aluminum current collector. The aluminum current collector is optionally in the form of a sheet formed of Al or an aluminum alloy, and can be in the form of a foil, a solid substrate, a porous substrate, a grid, a foam or a foam coated with Al, or other forms known in the art. In some aspects, the aluminum current collector is a foil. Optionally, the grid may include a porous metal mesh (expanded metal grid) and a porous foil mesh (perforated foil grid).
[0058] The positive electrode can include a current collector. The current collector for the positive electrode can be formed of aluminum, such as an aluminum alloy. The aluminum current collector is optionally in the form of a sheet, and can be in the form of a foil, a solid substrate, a porous substrate, a grid, a foam or an Al-coated foam, or other forms known in the art. In some aspects, the aluminum current collector is a foil. Optionally, the grid can include a porous metal mesh and a porous foil mesh.
[0059] The current collector for the anode or cathode is optionally associated with a tab, which can be used to electrically connect the battery to a circuit for use. The anode current collector and the cathode current collector can each be associated with a tab. The tab can be made of any suitable material, such as aluminum or other materials known in the art. The tab is optionally an uncoated area of the current collector. For stacked batteries with multiple anodes and cathodes, the tabs can be welded together to form a single positive tab and a single negative tab to connect to an external circuit.
[0060] The cathode in the electrochemical cell as provided herein is used as the positive electrode. The cathode comprises a polycrystalline cathode electrochemically active material capable of absorbing and desorbing Li. The cathode electrochemically active material as provided herein is of the formula Li 1+x MO 2+y A material wherein -0.9≤x≤0.3, -0.3≤y≤0.3, and wherein M comprises 80 atomic % or more Ni relative to the total M. The polycrystalline material comprises an agglomeration or association of a plurality of crystallites to form a polycrystalline material. Within the polycrystalline material, each crystallite may have any suitable shape, which may be the same or different within each secondary particle of the cathode electrochemically active material. In addition, the shape of each crystallite may be the same or different in different particles. Due to its crystalline nature, the crystallite may be faceted, the crystallite may have multiple planes and the shape of the crystallite may approximate a geometric shape. The crystallite may optionally be a polyhedron. The crystallite may have a rectilinear shape and when viewed in cross section, a portion or the entirety of the crystallite may be rectilinear. The crystallite may be square, hexagonal, rectangular, triangular or a combination thereof.
[0061] The cathode electrochemically active material includes Ni as the main M component. The amount of Ni in the first composition is optionally 80 atomic % to 100 atomic % (at%) of the total M. Optionally, the Ni component of M is greater than or equal to 80 at%. Optionally, the Ni component of M is greater than or equal to 85 at%. Optionally, the Ni component of M is greater than or equal to 90 at%. Optionally, the Ni component of M is greater than or equal to 95 at%. Optionally, the Ni component of M is greater than or equal to 75at%, 76at%, 77at%, 78at%, 79at%, 80at%, 81at%, 82at%, 83at%, 84at%, 85at%, 86at%, 87at%, 88at%, 89at%, 90at%, 91at%, 92at%, 93at%, 94at%, 95at%, 96at%, 97at%, 98at%, 99at%, 99.5at%, 99.9at% or 100at%.
[0062] In some aspects, M is Ni alone or in combination with one or more additional elements. The additional elements are optionally metals. Optionally, the additional elements may include or be one or more of Al, Mg, Co, Mn, Ca, Sr, Zn, Ti, Y, Cr, Mo, Fe, V, Si, Ga, or B. In particular aspects, the additional elements may include Mg, Co, Al, or a combination thereof. Optionally, the additional elements may be Mg, Al, V, Ti, B, or Mn, or a combination thereof. Optionally, the additional elements are selected from Mg, Al, V, Ti, B, or Mn. Optionally, the additional elements are selected from Mg, Co, and Al. Optionally, the additional elements are selected from Ca, Co, and Al. In some aspects, the additional elements are Mn or Mg, or Mn and Mg. Optionally, the additional elements are Mn, Co, Al, or any combination thereof. Optionally, the additional elements include Co and Mn. Optionally, the additional elements are Co and Al. Optionally, the additional element is Co.
[0063] The additional element of M in the cathode electrochemically active material can be present in an amount of about 0.1 to about 20 at%, especially about 5 to about 20 at%, more especially about 10 to about 20 at% of M in the first composition. Optionally, the additional element can be present in an amount of about 1 to about 20 at%, especially about 2 to about 18 at%, more especially about 4 to about 16 at% of M in the first composition. In some exemplary examples, M is about 80-100 at% Ni, 0-15 at% Co, 0-15 at% Mn and 0-10 at% additional element.
[0064] The cathode electrochemically active material used in the cathode of the battery as provided herein includes Co, wherein the Co is unevenly distributed throughout, on or in the secondary particles of the cathode electrochemically active material. The uneven distribution is a Co distribution that varies throughout some or all of the secondary particles. In some aspects, the polycrystalline material includes grain boundaries between adjacent crystallites within the secondary particles, wherein the concentration of cobalt, aluminum, or both is higher in the grain boundaries than in the center of the adjacent crystallites. Such materials are considered to be grain boundary enriched materials. Exemplary examples of such grain boundary enriched materials can be found in U.S. Patent No. 9,391,317 and U.S. Patent Application No: 16 / 250,762.
[0065] In certain aspects, such as secondary particles used as cathode electrochemically active materials, have grain boundaries enriched in Co, Al, or both, optionally wherein the mole fraction of Co, Al, or both in the grain boundaries is higher than the mole fraction of Co, Al, or both in the crystallites - optionally averaged overall by the sum of the regions.
[0066] The crystallites, grain boundary regions, or a combination of both optionally have a layered α-NaFeO2 type structure, a cubic structure, or a combination thereof. Specifically mentioned is one aspect, wherein the grain boundaries have a layered α-NaFeO2 type structure. Specifically mentioned is another aspect, wherein the grain boundaries have a defective α-NaFeO2 type structure. Specifically mentioned is another aspect, wherein a portion of the grain boundaries have a cubic structure or a spinel structure.
[0067] The grain boundaries are optionally composed of the formula I Li 1+x MO 2+y (Formula 1) The second composition is formed, wherein -0.9≤x≤0.3, -0.3≤y≤0.3, and wherein M includes Co, Al or a combination of Co and Al. Optionally, M in the second composition further includes Ni. Optionally, the Ni component of M in the second composition is less than or equal to 1at%. Optionally, the Ni component of M is less than or equal to 5at%. Optionally, the Ni component of M is less than or equal to 10at%. Optionally, the Ni component of M is less than or equal to 20at%. Optionally, the Ni component of M is less than or equal to 75at%. Optionally, the Ni component of M is less than or equal to 80at%. Optionally, the Ni component of M is less than or equal to 90at%. Optionally, the Ni component of M is less than or equal to 95at%. Optionally, the Ni component of M is less than or equal to 98at%. Optionally, the Ni component of M is less than or equal to 99at%.
[0068] In the cathode electrochemically active material enriched in grain boundaries, the concentration of Co, Al, or both averaged through the grain boundary region is higher than the average concentration of Co, Al, or both averaged through the crystallite region. Thus, the mole fraction of Co, Al, or both in the grain boundaries is higher than the mole fraction of Co, Al, or both in the crystallites. If Co, Al, or both are present in crystallites, the mole fraction of Co, Al, or both in the first composition as defining the crystallite composition is lower than the mole fraction of the total Co or Al (individually or in combination) in the total particle composition as determined by ICP. The mole fraction of Co and Al (individually or in combination) in the crystallites may be 0. The mole fraction of Co and Al (individually or in combination) in the second composition as defining the grain boundaries is higher than the mole fraction of Co and Al (individually or in combination) in the total particles as measured by ICP. The second composition may be enriched in Co at or between 0 to 8 at%, optionally at or between 3 to 5 at% Co and may optionally be supplemented with 0.01 to 10 at% Al, optionally 1.5 at% or less Al.
[0069] Optionally, the second composition is identical to the first composition (microcrystalline composition) except for the presence or concentration (molar fraction) of Co, Al, or both in the second composition relative to the first composition.
[0070] The cathode electrochemically active material optionally includes an inhomogeneous distribution of Co within the secondary particles, wherein the inhomogeneous distribution is in the form of a gradient of Co within the crystallite, within the total secondary particles, or a combination thereof. Optionally, the crystallite includes a gradient of Co concentration, wherein the amount of Co at or near the periphery of the crystallite is greater than the Co concentration at or near the center of the crystallite. Exemplary examples of such materials can be found in Lim et al., Adv. Funct. Mater. 2015; 25: 4673–4680 or Lee et al., Journal of Power Sources, 2015; 273: 663-669.
[0071] In some aspects, the non-uniform distribution of Co is achieved by coating the core with Co, as described in U.S. Patent No: 7,381,496, U.S. Patent Application Publication No: 2016 / 0181611, or Zuo et al., Journal of Alloys and Compounds, 2017; 706: 24-40.
[0072] The positive electrode may be provided by combining lithium nickel oxide, a conductive agent and a binder and providing a coating comprising lithium nickel oxide, a conductive agent and a binder on a current collector. The conductive agent may be any conductive agent that provides suitable properties and may be amorphous, crystalline or a combination thereof. The conductive agent may include carbon black, such as acetylene black or lamp black, mesocarbon, graphite, carbon fiber, carbon nanotubes such as single-walled carbon nanotubes or multi-walled carbon nanotubes or a combination thereof.
[0073] Binders for the anode or cathode can be any binder that provides suitable properties and can include, but are not limited to, polyvinylidene fluoride, copolymers of polyvinylidene fluoride, polyvinylidene fluoride (PVDF), hexafluoropropylene, poly(vinyl acetate), poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate), poly(methyl methacrylate-co-ethyl acrylate), polyacrylonitrile, polyvinyl chloride-co-vinyl acetate, polyvinyl alcohol, poly(l-vinyl pyrrolidone-co-vinyl acetate), cellulose acetate, polyvinyl pyrrolidone, polyacrylates, polymethacrylates, polyolefins, polyurethanes, polyvinyl ethers, acrylonitrile-butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene-styrene, triblock polymers of sulfonated styrene / ethylene-butylene / styrene, polyethylene oxide, or combinations thereof.
[0074] The positive electrode can be manufactured by combining lithium nickel oxide, a conductive agent and a binder in a suitable ratio, for example, 80 to 99 weight % of lithium nickel oxide, 0.5 to 20 weight % of the conductive agent and 0.5 to 10 weight % of the binder based on the total weight of the lithium nickel oxide, the conductive agent and the binder. The lithium nickel oxide, the conductive agent and the binder can be suspended in a suitable solvent, such as N-methylpyrrolidone or other suitable solvents and arranged on a suitable substrate, such as aluminum foil, and dried in air to provide a positive electrode.
[0075] The electrochemical cell as provided herein further comprises a negative electrode. The negative electrode comprises a positive electrode having a voltage of 400 mV or higher vs Li / Li + Optionally, the negative electrochemically active material vs Li / Li + The redox potential is 400mV or higher, optionally 500mV or higher, optionally 600mV or higher, optionally 700mV or higher, optionally 800mV or higher, optionally 900mV or higher, optionally 1V or higher, optionally 1.1V or higher, optionally 1.2V or higher, optionally 1.3V or higher, optionally 1.4V or higher, optionally 1.5V or higher, optionally 1.55V or higher, optionally 1.6V or higher.
[0076] Illustrative examples of negative electrochemically active materials include, but are not limited to, oxides of Nb, Sn, Sb, Ti, Si, and combinations thereof, as long as the material has a voltage of 400 mV or higher vs Li / Li + Specific illustrative examples can be found in Han and Goodenough, Chemistry of Materials, 23, no. 15 (2011): 3404-3407.
[0077] In some aspects, the negative electrochemically active material comprises an oxide of Nb. Exemplary examples include, but are not limited to, Nb 16 W5W 55 , Nb 18 W 16 O 93 , TiNb2O7, Ti2Nb2O9, LiTiNbO5, KNb5O 13 and K6Nb 10.8 O 30 Such materials are optionally those described in Griffith et al., Nature, 559, no. 7715 (2018): 556-563.
[0078] Other examples of oxides that can be used as negative electrochemically active materials include SnO2, Sb2O3, SiO, SiO2, and conversion anodes, provided that the negative electrochemically active material is characterized by 400 mV vs Li / Li + redox potential.
[0079] In some aspects, the negative electrochemically active material comprises an oxide of Ti. The oxide of Ti can be in any form, optionally including nanowires, such as the TiO2-B nanowires described by Armstrong et al., Journal of Power Sources, 146, no. 1-2 (2005): 501-506.
[0080] An exemplary example of a titanium oxide is lithium titanium oxide (LTO), optionally with a potential greater than 1 V vs Li / Li + , choose about 1.5V vs Li / Li + The lithium titanium oxide may have a spinel structure. The anode may include an optional Li 4+a Ti5O 12+b (2) The anode electrochemically active material, wherein -0.3≤a≤3.3, -0.3≤b≤0.3. In some aspects, the lithium titanium oxide may be of formula 3
[0081] Li 4+y Ti5O 12 (3)
[0082] Among them, 0≤y≤3, 0.1≤y≤2.8 or 0≤y≤2.6.
[0083] Alternatively, the lithium titanium oxide may be of formula 4
[0084] Li 3+z Ti 6-z O 12 (4)
[0085] Wherein in Formula 4, 0≤z≤1. Optionally, 0≤z≤1, 0.1≤z≤0.8 or 0≤z≤0.5. Combinations comprising at least one of the above lithium titanium oxide anode electrochemically active materials can be used. In some aspects, the anode electrochemically active material comprises or has a voltage of about 1.55 V vs Li / Li + Electrochemical redox potential of Li4Ti5O 12 .
[0086] The anode electrochemically active material may have any suitable particle size, such as a particle size of 0.1 μm to 100 μm or 1 μm to 10 μm.
[0087] The anode electrochemically active material may have a high specific surface area (SSA), such as 4 m2 / g to 20m 2 / g or 7m 2 / g to 13m 2 / g.
[0088] As discussed further above, although not wishing to be bound by theory, it is understood that since the electrochemical potential of the anode electrochemically active material is equal to or greater than 400 mV vs Li / Li + , the negative electrode current collector may include a metal other than copper, because other metals, such as aluminum and titanium, have a current density equal to or higher than 400 mV vs Li / Li + The electrochemical redox potential of the anode electrochemically active material is preferably provided at a potential of 0.1V to 0.5V vs. Li / Li, while copper is not, which is why copper is used as the current collector material when graphite is used as the anode material. Therefore, the electrochemically active material having an electrochemical redox potential of 0.1V to 0.5V, 0.15V to 0.45V, or 0.2V to 0.4V vs. Li / Li is preferably provided at a potential of 0.1V to 0.5V, 0.15V to 0.45V, or 0.2V to 0.4V vs. Li / Li. + Current collectors of metals that can electrochemically react with lithium at potentials of 20 Å to 40 Å may not be used for graphite anode materials, but can be used for anode materials as provided herein.
[0089] The current collector of the anode, cathode, or both may include aluminum, preferably aluminum or an aluminum alloy. Representative aluminum alloys include aluminum alloys 1050, 1100, 1145, 1235, 1350, 3003, 3105, 5052, and 6061.
[0090] The negative electrode can be provided by combining an anode electrochemically active material, a conductive agent and a binder and providing a coating comprising the anode electrochemically active material, the conductive agent and the binder on a current collector selected for the negative electrode. The conductive agent can be any conductive agent that provides suitable properties and can be amorphous, crystalline or a combination thereof. The conductive agent can be carbon black, such as acetylene black or lamp black, mesophase carbon, graphite, carbon fiber, carbon nanotubes such as single-walled carbon nanotubes or multi-walled carbon nanotubes or a combination thereof. The binder can be any binder that provides suitable properties and can include, for example, polyvinylidene fluoride, PVDF, hexafluoropropylene, copolymers of polyvinylidene fluoride and hexafluoropropylene, poly(vinyl acetate), poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate), poly(methyl methacrylate-co-ethyl acrylate), polyacrylonitrile, polyvinyl chloride-co-vinyl acetate, polyvinyl alcohol, poly(l-vinyl pyrrolidone-co-vinyl acetate), cellulose acetate, polyvinyl pyrrolidone, polyacrylates, polymethacrylates, polyolefins, polyurethanes, polyvinyl ethers, acrylonitrile-butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene-styrene, triblock polymers of sulfonated styrene / ethylene-butylene / styrene, polyethylene oxide, or combinations thereof.
[0091] The negative electrode can be manufactured by combining the anode electrochemically active material, the conductive agent and the binder in a suitable ratio, for example, 80 to 98 weight % of the anode electrochemically active material, 2 to 20 weight % of the conductive agent and 2 to 10 weight % of the binder based on the total weight of the anode electrochemically active material, the conductive agent and the binder. The anode electrochemically active material, the conductive agent and the binder can be suspended in a suitable solvent, such as N-methylpyrrolidone and arranged on a suitable current collector, such as aluminum, titanium or stainless steel, and dried in air to provide the negative electrode.
[0092] The positive and negative electrodes can be prepared at loadings (mass of coating material per unit area of current collector) that are tailored to the desired rate performance and voltage range for a specific application. Higher power (high rate) applications require lower loading electrodes to maximize the electrode interface surface area and minimize current density, while applications requiring higher energy density require higher loading electrodes to minimize the content of inactive materials such as current collectors and separators in the battery.
[0093] With equal to or greater than 400mV vs Li / Li +A further advantage of an anode electrochemically active material having an electrochemical redox potential of 1000 Å is that it can be implemented in an anode-limited cell design because its potential is positive enough to avoid the possibility of lithium metal precipitation under almost the most extreme overcharge conditions. Such an anode-limited cell design can enhance the overcharge tolerance and stability of the cell by limiting the delithiation of the charging cathode to a level commensurate with each cell voltage required for a specific application. Thus, the electrochemical cell as provided herein is optionally limited in area, loading or other aspects.
[0094] Optionally, the electrochemical cell is anode limited in that the geometric surface area of the cathode is optionally greater than or equal to the geometric surface area of the anode. Thus, the area ratio equal to the area of the negative electrode divided by the area of the positive electrode is less than or equal to 1. Optionally, the area ratio of the anode to the cathode is less than or equal to 0.99, 0.98, 0.97, 0.96, 0.95, 0.94, 0.93, 0.92, 0.91, 0.90, 0.85, 0.80, 0.75, 0.70, 0.65, 0.60, 0.55 or 0.50. In some aspects, the geometric areas of the positive and negative electrodes are equal or substantially equal.
[0095] Optionally, the capacity ratio of the anode to the cathode is less than or equal to 1. The electrode capacity ratio is the ratio of the negative electrode solvent to the positive electrode capacity. The capacity of the electrode is usually given as the charge-time product per unit area. The units of charge and time used are not important in the ratio calculation. The capacity of the electrode is equal to the capacity per unit area multiplied by the electrode area. Therefore, at similar areas of the two electrodes, the capacity ratio is equal to the ratio of the capacitance per unit area of the two electrodes. Optionally, the capacity ratio of the anode to the cathode is less than or equal to 0.99, 0.98, 0.97, 0.96, 0.95, 0.94, 0.93, 0.92, 0.91, 0.90, 0.85, 0.80, 0.75, 0.70, 0.65, 0.60, 0.55 or 0.50.
[0096] The ideal anode / cathode (n / p) ratio depends on the exact cathode material used and the intended battery application. As provided herein, the maximum value of the n / p capacity ratio is less than 1 (e.g., 0.99) because an n / p ratio of less than 1 can maximize the benefits. At the other extreme, an n / p ratio of less than 0.5 significantly limits the commercial viability of the battery because it means that only 50% of the capacity of the cathode material is utilized. Between 0.5 and 0.99, it is easy for the battery designer to determine where to limit the upper cutoff voltage of the cathode material. For example, cathode instability, side reactions, or electrolyte decomposition can begin at 4.2V vs Li / Li + Therefore, for a battery as provided herein, the voltage is optionally limited to 4.1 V vs Li / Li +To achieve a long life battery. The required n / p ratio can be determined by the following equation:
[0097]
[0098] Where Q 最大电压 is the capacity of the cathode material at the maximum voltage during charging, and Q 电压极限 It is the capacity of the cathode material at the voltage limit set during charging. From this equation, it can be determined that the optimal capacity n / p ratio is less than 1, and is optionally 0.5 to 0.99, optionally 0.7 to 0.99, optionally 0.8 to 0.99, optionally 0.8 to 0.97, optionally 0.8 to 0.96, optionally 0.8 to 0.95, optionally 0.85 to 0.99, optionally 0.85 to 0.97, optionally 0.85 to 0.95, optionally 0.9 to 0.99, optionally 0.9 to 0.97, and optionally 0.9 to 0.95.
[0099] In some aspects of the provided electrochemical cell, the unit cell comprises an anode, a cathode and a separator between the anode and the cathode, wherein an electrolyte in ionic contact with the anode and cathode is provided. Optionally, the unit cell comprises a double-sided anode, wherein the anode electrochemically active material is coated on both sides of the current collector, or wherein the cathode is a double-sided cathode, wherein the current collector is coated with the cathode electrochemically active material on both sides. The double-sided electrode may have two single-sided opposite electrodes on both sides, or another opposite double-sided electrode. Thus, a stack of electrodes may be provided to form a unit cell. In some aspects, two single-sided anode electrodes comprising an anode electrochemically active material coated on an aluminum current collector, a polyolefin separator and a double-sided cathode electrode coated on both sides of the aluminum current collector are provided. Such unit cells are stacked to form an electrochemical cell. In some aspects, the single-sided anode electrode is located at the end of such a stack, but it is recognized that the end electrode of the stack can be a cathode.
[0100] The positive electrode, negative electrode and separator can be combined in a housing to provide a lithium ion battery, one aspect of which is shown in Figure 1 The lithium-ion battery 100 includes: a positive electrode 101 having a positive electrode tab 101'; a negative electrode 102 having a negative electrode tab 102'; and a separator 103 between the positive electrode 101 and the negative electrode 102. The battery may include an electrolyte in ionic contact with both the anode and the cathode. Ionic contact means that the electrolyte can transfer ions from the anode to the cathode or from the cathode to the anode.
[0101] The electrochemical cell includes a separator located between the anode and cathode in the unit cell. The separator can be formed of a microporous membrane, optionally a porous membrane comprising a polyolefin, such as polypropylene, polyethylene or a combination thereof. In some aspects, the separator can further include a ceramic oxide material, optionally a coating of aluminum oxide or a particulate reinforcing filler. A high permeability separator having a Gurley air permeability of less than 200 seconds / 100cc can be selected to provide a battery with high power capabilities.
[0102] The anode, cathode, separator and electrolyte can be contained in a battery housing (e.g., housing). The battery housing 110 can be a metal can, or can be a laminated film, such as a heat-sealable aluminum foil, such as an aluminum-coated polypropylene film. Thus, the electrochemical cell as provided herein can be any known battery form, such as a button cell, a soft pack battery, a cylindrical battery, or other suitable configuration. In some aspects, the housing is a flexible film, optionally in the form of a polypropylene film. Such housings are commonly used to form soft pack batteries. The lithium-ion battery can have any suitable configuration or shape, and can be cylindrical or square.
[0103] Batteries as provided herein optionally do not include any circuitry, such as battery management circuitry or other devices capable of regulating the charge rate or degree of charge or discharge and used in the art.
[0104] The lithium ion battery includes an electrolyte contacting a positive electrode 101, a negative electrode 102 and a separator 103. The electrolyte may include an organic solvent and a lithium salt. The organic solvent may be a mixture of a cyclic carbonate and a linear carbonate. Representative organic solvents include ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, methyl butyrate or a combination thereof. A mixture of propylene carbonate, ethyl methyl carbonate and methyl butyrate is mentioned.
[0105] Representative lithium salts used in the electrolyte include, but are not limited to, LiPF6, LiBF4, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiN(SO2C2F5)2, LiSbF6, LiC(CF3SO2)3, LiC4F9SO3, and LiAlCl4. The lithium salt may be dissolved in an organic solvent. A combination comprising at least one of the above salts and a solvent may be used. The concentration of the lithium salt in the electrolyte may be 0.1 to 2 molar (M). A 1M LiPF6 solution is mentioned.
[0106] The electrolyte may be formulated to provide high power capability and low temperature performance.Such an electrolyte may have an ionic conductivity greater than 8 mS / cm at 25°C and greater than 1 mS / cm at -40°C.
[0107] A battery pack made from the lithium-ion battery can include any suitable number of cells, such as 1 to 50,000 cells, 2 to 25,000 cells, 4 to 15,000 cells, 8 to 5,000 cells, 16 to 2,000 cells, or 32 to 1,000 cells. The cells can be connected in any suitable configuration, including in series, in parallel, or a combination thereof.
[0108] The charging and discharging of the battery and the battery made therefrom may comprise any suitable charging and discharging method and may comprise charging and discharging at any suitable rate, such as 100C or less, 10C or less, 0.01C to 10C, or 0.1C to 1C. The C rate is the discharge rate of the battery and is obtained by dividing the total capacity of the battery by the total discharge time, for example, the C rate of a battery having a discharge capacity of 1.6 ampere-hours is 1.6 amperes. Discharging may comprise discharging the battery to 1.4V or less, optionally 1.3V or less, optionally 1.2V or less, optionally 1.1V or less, optionally 1.0V or less, optionally 0.9V or less, optionally 0.8V or less, optionally 0.7V or less, optionally 0.6V or less, optionally 0.5V or less, optionally 0.4V or less, optionally 0.3V or less, optionally 0.2V or less, optionally 0.1 volt or less, such as 0.1V to 0.001V, 0.05V to 0.005V. Discharging is optionally to 0V or less.
[0109] Various aspects of the present disclosure are illustrated by the following non-limiting examples. These examples are used to illustrate but not to limit any practice of the present invention. It is to be understood that changes and modifications can be made without departing from the spirit and scope of the present invention. Example
[0110] Example 1
[0111] By setting the nominal composition to Li 1.01 Mg 0.025 Ni 0.88 Co 0.12 Al 0.0064 O2-rich cobalt grain boundary LNO-type lithium nickel oxide (CAMX Power, LLC, Lexington, MA), acetylene black and polyvinylidene fluoride (PVDF) in a 94:3:3 weight ratio mixture were added at 11.3 mg / cm 2 The positive electrode is made by coating aluminum with an active material loading of Li4Ti5O 12 The nominal composition and has 10m 2 / g specific surface area of lithium titanium oxide, acetylene black and PVDF in a weight ratio of 90:3:7 at 12.7 mg / cm 2The active material loading of 100 m was coated on aluminum to make the negative electrode. 2 Acetylene black (from Denka Carbons as Denka AB-100) having a surface area of 100 mol / g and PVDF (from Solvay Chemicals as Solef 5130) having a molecular weight of 1,000,000-1,200,000 mol / g.
[0112] The positive and negative electrodes have a 72.7 cm 2 of equal geometric area. 12 layers of double-sided positive electrodes are stacked with 11 layers of double-sided negative electrodes and 2 layers of single-sided negative electrodes in a Z-folded separator assembly. The separator is a 21 μm thick alumina-coated polyolefin material with a Gurley permeability of 110 seconds. The electrode stack assembly is placed in an aluminum-coated polypropylene shell, the electrode tabs are sealed through the edge of the package, and before sealing, an electrolyte consisting of 1M LiPF6 in a mixture of 1:1:2 weight ratio of propylene carbonate, ethyl methyl carbonate and methyl butyrate and having an ionic conductivity of 11mS / cm at 25°C and 2mS / cm at -40°C is added to provide a 3 ampere-hour (Ah) laminated packaged square battery weighing 82g.
[0113] The cell was cycled at room temperature at various rates between 2.75 V and 1.4 V. It was also cycled at -50°C at various rates between 3.0 V and 1.2 V.
[0114] Figure 2 is a graph of cell voltage (volts, V) vs. capacity (ampere-hours, Ah) illustrating the voltage curves for the first charge and discharge of the cell at a rate of 0.6A and subsequent charge and discharge at rates of 3A and 9A, which were conducted at room temperature. The 0.6A first charge voltage curve shows an upward bend at about 2.55V, characteristic of the anode-limited charge capacity of this design. The cell has high rate capability as evidenced by the modest increase in voltage polarization as the current increases from 0.6A (C / 5) to 9A (3C).
[0115] Figure 3 is a graph of cell voltage (volts, V) vs. capacity (ampere-hours, Ah) illustrating the voltage curves of cells charged and discharged at various rates at -50°C, demonstrating high levels of performance at temperatures well outside the range achievable with conventional lithium-ion battery technology. Figure 4) expands the voltage limit to accommodate the higher voltage polarization at this extreme low temperature. The battery delivers well over half of its capacity when discharged at 0.6A, and over 40% of its capacity when discharged at 10C. Remarkably, the battery can be charged to almost half of its capacity at a 3A (1C) rate within a 3V charging voltage limit.
[0116] Example 2
[0117] Two 120 mAh laminated packaged prismatic cells were made using the materials and methods of Example 1, but with the following differences:
[0118] The positive electrode active material loading is 9.0 mg / cm 2 The negative electrode active material loading is 9.4 mg / cm 2 . The single cathode and anode pieces are both 10.2cm 2 area, and assembled in a stack of 5 layers of bifacial positive electrodes and 4 layers of bifacial negative electrodes + 2 layers of single-sided negative electrodes. The batteries were first cycled between 2.43V and 1.33V at room temperature, equivalent to a 6-series battery pack cycling between 14.6V and 8.0V. They were then cycled 1,000 times between 2.43V and 1.33V in a 45°C oven at a 1.2A (10C) charge rate and a 1.2A (10C) discharge rate. The batteries were free-standing during this cycling process, without any external clamps to maintain stack pressure as they evolved gas. Inspection and measurement of the batteries after the cycling was completed showed no signs that they had released any gas.
[0119] Figure 4 is a plot of the 1OC discharge capacity vs. cycle number of the two cells during cycling at 45°C, and shows that the capacity delivered by the cells decays by only about 5% during this aggressive cycling regime, confirming that the cells have excellent high temperature stability and that they are not damaged by repeated fast charging.
[0120] Example 3
[0121] A 325 mAh laminated packaged prismatic cell designed for very high power capability was fabricated using the materials and methods of Example 1, but with the following differences:
[0122] The positive electrode active material loading is 3.6 mg / cm 2 The negative electrode active material loading is 3.7 mg / cm 2 . Single cathode and anode pieces are 10.2cm 2area, and assembled in a stack of 36 layers of bifacial positive electrode and 35 layers of bifacial negative electrode + 2 layers of single-sided negative electrode. The separator is a 6 μm thick polyolefin material with a Gurley permeability of 100 seconds. The final battery weighs 13.5 g and has a volume of 7.2 cc.
[0123] At various constant power levels, the cells were cycled between 2.59 V and 1.31 V at room temperature, which is equivalent to cycling between 28.5 V and 14.4 V for an 11-series cell battery pack. Figure 5 2 graphs showing the voltage (volts, V) vs. capacity (mAh) for charging and discharging of the battery at various power levels, and demonstrating the very high power capability of the battery. At 80W constant power - equivalent to more than 5kW / kg constant specific power and more than 11kW / l power density, the battery maintained continuous charging for nearly 30 seconds and maintained continuous discharge for about 11 seconds, outputting about 45% of its capacity and 18.5Wh / kg, constituting about 35% of its total energy content.
[0124] Example 4
[0125] A 3-electrode 130 mAh laminated packaged prismatic cell containing a Li metal reference electrode was fabricated using the materials and methods of Example 1, but with the following differences:
[0126] The positive electrode active material loading is 9.1 mg / cm 2 The negative electrode active material loading is 10.0 mg / cm 2 . Single cathode and anode pieces are 10.2cm 2 area, and assembled in a stack of 5 layers of double-sided positive electrodes and 4 layers of double-sided negative electrodes + 2 layers of single-sided negative electrodes.
[0127] The cell performance was characterized by constant current continuous and pulse charge / discharge cycles between 2.59 V and 1.31 V at room temperature and at -18°C, and the cathode potential was monitored by measuring the positive electrode vs. Li metal reference electrode voltage as the cell cycled, and the anode (negative electrode) potential was calculated by the difference between the cathode potential and the cell voltage. The cell was then discharged to 0 V and held at that voltage for 24 hours, after which it was subjected to a voltage reversal by overdischarging it at a 0.1C rate by an additional 5% (6.5 mAh) of its capacity (i.e., 13 mA discharge for 30 minutes). After reversal, the cell was recharged and its performance was recharacterized.
[0128] Figure 630 minutes duration and then relax (relaxation) under open circuit for 30 minutes, the electrode potential (V vs. Li reference) and the cell voltage vs. time (minutes) curve. The curve shows that the cell voltage reverses and reaches about -3.5V, and the cathode and anode potentials reach about 1.9V vs. Li and 5.4V vs. Li, respectively. Under open circuit, the cell voltage increases rapidly, mainly due to the rapid decrease of the high anode potential, while the low cathode potential increases much more slowly, indicating that the voltage polarization at the anode is greater than that at the cathode during overdischarge and cell reversal, and that the charge transferred by the cathode during overdischarge is associated with a reversible Faradaic process.
[0129] Figure 7 is a graph of voltage (volts) vs. capacity (Ah) for various discharge rates of a battery at room temperature before and after its reversal, and shows that a 5% capacity reversal has minimal effect on room temperature discharge characteristics.
[0130] Figure 8 is a graph of voltage (volts) vs. capacity (mAh) for a battery at -18°C before and after its reversal for a continuous 10C (1.3A), 30 second duration pulse discharge. The battery was left to rest at open circuit for 30 minutes after each pulse (before the next pulse) to ensure that it did not significantly self-heat during the test. The battery was able to support this severe low temperature pulse over 50% of its state of charge range (65mAh) both before and after the reversal, indicating that the 5% capacity reversal had minimal effect on the low temperature pulse power performance.
[0131] Example 5
[0132] A 3-electrode 130 mAh laminated packaged square cell containing a Li metal reference electrode was fabricated using the materials and methods of Example 4. The cell performance was characterized by constant current continuous and pulsed charge / discharge cycles between 2.59 V and 1.31 V at room temperature and at -18°C, and the cathode potential was monitored as the cell cycled by measuring the positive electrode vs. Li metal reference electrode voltage, with the anode (negative electrode) potential calculated by the difference between the cathode potential and the cell voltage. The cell was then charged to 2.59 V, after which it was overcharged an additional 10% (13 mAh) of its capacity at a 0.1C rate (i.e., 13 mA charging for 60 minutes). After overcharging, the cell was discharged and its performance was recharacterized.
[0133] Fig. 9is a graph of electrode potential (V vs. Li reference) and cell voltage vs. time (min) for a cell overcharged for a duration of 60 minutes and then relaxed at open circuit for 30 minutes. The graph shows that the overcharged cell voltage reaches about 3.5 V, and the cathode and anode potentials reach about 4.1 V vs. Li / Li, respectively. + and 0.6V vs.Li / Li + Under open circuit, the cell voltage decreases due to the increase in anode potential, while the cathode potential remains unchanged, indicating that the voltage polarization at the anode is greater than that at the cathode during overcharge, and that the charge transferred by the cathode during overcharge is related to its normal reversible Faradaic process, as expected for an anode-limited cell design with about 20% excess cathode.
[0134] Fig.10 It is a graph of voltage (volts) vs. capacity (Ah) for various discharge rates of the battery at room temperature before and after its reversal, and shows that 10% overcharge has little effect on the room temperature discharge characteristics. The voltage polarization during 25C discharge is greater after overcharge than before, indicating that overcharge slightly increases the impedance of the battery.
[0135] Fig.11 is a graph of voltage (volts) vs. capacity (mAh) of a battery subjected to continuous 10C (1.3A), 30 second duration pulse discharge at -18°C before and after it was overcharged. The battery was left to rest at open circuit for 30 minutes after each pulse (before the next pulse) to ensure that it did not significantly self-heat during the test. The battery was able to support such low temperature pulses over a 65mAh depth of discharge range before overcharge and over a 50mAh depth of discharge range after reversal, while the voltage polarization during the pulses was higher after overcharge. The results of these severe low temperature pulse tests indicate that overcharge increases the impedance of the battery, but the battery still maintains a high level of performance.
[0136] Example 6
[0137] A 2.5 Ah laminated packaged prismatic cell was fabricated using the materials and methods of Example 1, but with the following differences.
[0138] The positive electrode active material loading is 11.2 mg / cm 2 The negative electrode active material loading is 12.6 mg / cm 2 . Single cathode and anode piece is 72.7cm 2 area, and assembled in a stack of 10 layers of double-sided positive electrodes and 9 layers of double-sided negative electrodes + 2 layers of single-sided negative electrodes.
[0139] The battery was first charged to 2.75V at 0.5A and then cycled between 2.75V and 1.4V at various rates to evaluate its performance. The battery was then cycled 1,000 times between 2.65V and 1.4V at a 2.5A (1C) charge rate and a 2.5A (1C) discharge rate at room temperature. During this cycling process, the battery continuously maintained a 2.2Ah capacity. After 1,000 cycles, the battery was discharged to 0V and stored at room temperature for 33 months. After this storage, the battery open circuit voltage was measured to be 0V, and then the battery was charged and cycled by the same procedure used to characterize it when it was newly built.
[0140] Fig.12 is a graph of voltage (volts) vs. capacity (Ah) at various rates of discharge at room temperature for a battery before and after it was cycled 1,000 times and subsequently stored at 0V for 33 months, and shows that cycling and long-term 0V storage do not substantially change the performance of the battery. These results demonstrate the excellent cycling stability and storage life at 0V for this battery technology. The graph also shows that the first charge at 0.5A after long-term 0V storage essentially replicates the first charge at 0.5A of a newly made battery, indicating that discharging to 0V restores the battery to its as-made condition.
[0141] Example 7
[0142] A 2.7 Ah laminated packaged prismatic cell was fabricated using the materials and methods of Example 1, but with the following differences.
[0143] The positive electrode active material loading is 8.4 mg / cm 2 The negative electrode active material loading is 9.1 mg / cm 2 . Single cathode and anode piece is 72.7cm 2 area, and assembled in a stack of 15 layers of double-sided positive electrodes and 14 layers of double-sided negative electrodes + 2 layers of single-sided negative electrodes.
[0144] The cells were first charged to 2.65 V and then subjected to a nail penetration test in a custom designed apparatus by driving a blunt-tipped 2 millimeter (mm) diameter stainless steel nail into it at a rate of 1 cm / sec and keeping it in the cell for 1 minute while recording the cell's voltage and surface temperature. Fig.13It is a graph of the battery voltage (V) and surface temperature (°C) before, during, and after the nail penetration test. The graph shows that the voltage of the battery decreases very slowly while the nail is still in the battery, similar to the voltage change during low-rate discharge (e.g., <C / 10), indicating that a soft short has occurred. When the nail is removed, this voltage change stops, indicating that the short circuit has been cleared. Similarly, the surface temperature of the battery only increases very slightly during the nail penetration process. These results confirm that this battery technology significantly prevents the formation of high-power internal short circuits when subjected to piercing mechanical abuse.
[0145] Example 8
[0146] A 4 Ah laminated pouch square battery was fabricated using the materials and methods of Example 1, but with the following differences.
[0147] The positive electrode active material loading was 9.3 mg / cm 2 and the negative electrode active material loading was 9.0 mg / cm 2 .
[0148] The individual cathode and anode pieces had an area of 124.9 cm 2 and were assembled in a stack of 12 layers of double-sided positive electrode and 11 layers of double-sided negative electrode + 2 layers of single-sided negative electrode.
[0149] First, the performance of the battery was characterized by cycling it between 2.59 V and 1.31 V at various rates at room temperature, and then it was charged to 2.75 V. The charged battery was then squeezed for 5 minutes under a 1 / 2” diameter stainless steel bar placed across its 10 cm width in a custom-designed device while recording the battery's voltage and surface temperature. During the squeezing test, the force on the bar was increased to 35 kN (3.8 tons), and the displacement measured by the squeezing device indicated that the thickness of the battery decreased from 5 mm to 0.5 mm at the line of maximum crush. During the squeezing event, the battery voltage slowly decreased from 2.556 V to 2.552 V as in low-rate discharge, and the surface temperature increased by 1 °C. When the pressure on the bar and the battery was released, the voltage stopped dropping and the temperature stopped rising. Then, the performance of the battery was characterized again by cycling it between 2.59 V and 1.31 V.
[0150] Fig.14 It is a graph of the voltage (volts) vs. capacity (Ah) of the battery during discharge at two rates at room temperature before and after it was subjected to a round bar crush. The graph shows that the performance of the battery is not affected by the squeezing test, further confirming that this battery technology significantly prevents the formation of high-power internal short circuits when subjected to mechanical abuse.
[0151] Example 9
[0152] A 5 Ah laminated packaged prismatic cell was fabricated using the materials and methods of Example 1, but with the following differences.
[0153] The positive electrode active material loading is 9.5 mg / cm 2 The negative electrode active material loading is 9.1 mg / cm 2 . Single cathode and anode pieces are 141.9cm 2 area, and assembled in a stack of 16 layers of double-sided positive electrodes and 15 layers of double-sided negative electrodes + 2 layers of single-sided negative electrodes.
[0154] The battery of this embodiment has the following key elements:
[0155] a. A negative electrode comprising lithium titanium oxide (LTO) coated on an aluminum current collector. The coating is a 10 m 2 / g specific surface area of LTO, acetylene black as a conductive additive and PVDF as a binder in a weight ratio of 90:3:7. Acetylene black has a specific surface area of 100 m 2 / g surface area (from Denka as Denka AB-100), and PVDF (from Solef 5130 from Solvay) has a molecular weight of 1,000,000-1,200,000 mol / g. Acetylene black conductive carbon occupies less than 5% of the surface of the anode electrode. Uncoated aluminum strip forms the negative electrode tab.
[0156] b. A positive electrode comprising a Li 1.01 Mg 0.025 Ni 0.88 Co 0.12 Al 0.0064 High nickel cathode material for O2. The coating is a mixture of acetylene black and PVDF in a 94:3:3 weight ratio. Acetylene black has a 100m 2 / g surface area, and PVDF has a molecular weight of 1,000,000-1,200,000 mol / g. Uncoated aluminum strips form the positive electrode tabs.
[0157] c. 21 μm thick polyolefin separator, coated with alumina on one side and having a Gurley permeability of 110 seconds; the alumina side is placed next to the positive electrode.
[0158] d. The geometric areas of the positive and negative electrodes are equal.
[0159] e. Assembling an electrochemical cell using a stack of a double-sided negative electrode, a separator and a double-sided positive electrode;
[0160] f. The stacking is such that the positive electrode tabs overlap each other and are ultrasonically welded to each other and to the positive battery tabs, and the negative electrode tabs overlap each other and are ultrasonically welded to each other and to the negative battery tabs.
[0161] g. The terminal layer of the stack is the negative electrode;
[0162] h. An electrolyte having 1 M LiPF6 in a mixture of propylene carbonate, ethyl methyl carbonate and methyl butyrate in a 1:1:2 weight ratio and having an ionic conductivity of 11 mS / cm at 25°C and 2 mS / cm at -40°C.
[0163] The performance of the battery was characterized by 2A charge, 8A discharge cycles between 2.65V and 1.5V at room temperature, and then charged to 2.65V. The charged battery was then subjected to nail penetration testing 3 times in the manner of Example 7, and then crush testing 2 times in the manner of Example 8. An array of 3 parallel green LEDs contacted across the battery terminals remained illuminated during all 5 abuse tests. The performance of the abuse battery was then characterized again by 2A charge, 8A discharge cycles between 2.65V and 1.5V, and then the battery was continuously cycled between 2.65V and 1.4V at 5A charge and discharge rates.
[0164] Fig.15 is a photograph of the battery after abuse testing, with the LED still lit across its terminal contacts, and vividly demonstrating the remarkable abuse tolerance of this battery.
[0165] Fig.16 is a graph of voltage (volts) vs. capacity (Ah) of a battery discharged at 8A at room temperature before and after it was subjected to 5 abuse tests, which shows that the performance of the battery is not affected by repeated mechanical abuse.
[0166] Fig.17 is a graph of the discharge capacity of the cell vs. the number of cycles when charged / discharged at 5A / 5A in ambient atmosphere at room temperature after 5 abuse tests. The figure shows that the capacity output by the cell drops in about the first 5 days (50+ cycles), probably due to the loss of volatile solvent components of the electrolyte through the holes in the package caused by nail puncture. Thereafter, the cell cycles fairly stably at about 4Ah capacity for nearly 3 weeks without further significant capacity loss until more than 300 cycles have passed, at which time the cell performance degradation may be attributed to the gradual cumulative penetration of atmospheric humidity through the nail holes in the package. These results indicate that the only effect of severe puncture and crush abuse on cell performance can be attributed to package damage, further confirming the excellent robustness of this cell technology.
[0167] Example 10
[0168] A 2.5Ah laminated packaged square battery was manufactured according to the method of Example 9. The battery was charged to 2.75V at currents of 0.5A, 2.5A and 9.8A, respectively, and then discharged to 1.4V. The voltage-capacity curve can be seen at Fig.18 After this test, the battery was cycled between 1.4V and 2.75V for 1,000 cycles at a current of 2.5A in both charge and discharge. Next, the battery was discharged to 0V and stored for 33 months without connection and monitoring. After storage, the battery was charged to 2.75V and discharged to 1.4V at currents of 0.5A, 2.5A, and 9.8A, respectively. Fig.18 The solid line on the voltage-capacity graph represents the battery performance just after manufacturing, and the dotted line represents the performance after storage.
[0169] It is to be understood that, although the terms "first", "second", "third", etc. may be used herein to describe various elements, components, regions, layers and / or sections, these elements, components, regions, layers and / or sections should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or section from another element, component, region, layer or section. Therefore, the "first element", "component", "region", "layer" or "section" discussed below may be referred to as a second element, component, region, layer or section without departing from the teachings of this article.
[0170] The terms used herein are only used to describe specific aspects and are not intended to be limiting. Unless the context clearly indicates otherwise, the singular forms "one" and "the" used herein are intended to include plural forms, including "at least one". "Or" means "and / or". The term "and / or" used herein includes any and all combinations of one or more related enumerated items. It is also to be understood that the terms "comprising" or "including" when used in this specification specify the presence of the features, regions, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, regions, integers, steps, operations, elements, components and / or combinations thereof. The term "or a combination thereof" refers to a combination including at least one of the above elements.
[0171] Spatially relative terms, such as "below," "below," "lower," "above," "above," and the like, are used herein for ease of description to describe the relationship of one element or member to another element or member as shown in the accompanying drawings. It is to be understood that the spatially relative terms are intended to include different orientations of the device in use or operation in addition to the orientation depicted in the accompanying drawings. For example, if the device in the accompanying drawings is inverted, elements described as being "below" or "below" other elements or members are then oriented "above" the other elements or members. Thus, the exemplary term "below" can include both above and below orientations. The device can be oriented in other ways (rotated 90 degrees or other orientations) and the spatially relative descriptors used herein are interpreted accordingly.
[0172] Unless otherwise specified, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present disclosure belongs. It is also understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning consistent with their meanings in the relevant art and the present disclosure, and should not be interpreted in an idealized or overly formal sense, unless explicitly so specified herein.
[0173] Exemplary aspects are described herein with reference to cross-sectional views, which are schematic diagrams of idealized aspects. As such, variations in the illustrated shapes due to, for example, manufacturing techniques are contemplated. Therefore, the aspects described herein should not be construed as limited to the specific shapes of the regions as illustrated herein, but rather include shape deviations due to, for example, manufacturing. For example, a region illustrated or described as a plane may have rough and / or nonlinear features. In addition, illustrated sharp angles may be rounded. Therefore, the regions illustrated in the drawings are schematic and their shapes are not intended to show the precise shape of the region and are not intended to limit the scope of the claims.
[0174] Although the present disclosure describes exemplary aspects, it will be appreciated by those skilled in the art that various changes may be made and equivalents may be substituted for its elements without departing from the scope of the disclosed aspects. In addition, many modifications may be made to adapt specific situations or materials to the teachings of the present disclosure without departing from its scope. Therefore, the present disclosure is not intended to be limited to specific aspects disclosed as being considered as the best mode for implementing the present disclosure. It should also be understood that the aspects disclosed herein should be considered only in a descriptive sense and not for limitation. The description of the features, advantages or aspects of each aspect should be considered to be applicable to other similar features, advantages or aspects of other aspects.
[0175] Various modifications of the disclosure in addition to those shown and described herein will be apparent to those skilled in the art from the foregoing specification. Such modifications are also intended to fall within the scope of the appended claims.
[0176] It is to be appreciated that unless otherwise specified, all reagents and components are available from sources known in the art.
[0177] The patents, publications, and applications mentioned in the specification are indicative of the levels of those skilled in the art to which the invention relates. These patents, publications, and applications are hereby incorporated by reference as if each individual patent, publication, or application was specifically and individually incorporated by reference herein.
[0178] The above description is illustrative of particular aspects of the invention and is not intended to limit the practice thereof. The following claims, including all equivalents thereof, are intended to define the scope of the invention.
Claims
1. An electrochemical cell comprising: A cathode comprising a polycrystalline cathode electrochemically active material comprising a Li 1+x MO 2+y , wherein -0.9≤x≤0.3, -0.3≤y≤0.3, and wherein M comprises 80 atomic % or more Ni relative to total M, wherein the cathode electrochemically active material comprises a plurality of crystallites and grain boundaries between the plurality of crystallites, the cathode electrochemically active material comprises a non-uniform distribution of Co, Al, or both such that the concentration of Co, Al, or both is higher in the grain boundaries than in the center of adjacent crystallites, wherein the concentration of Al in the grain boundaries, when present, is from 0.01 atomic % to 10 atomic %; An anode comprising an electrochemically active material, wherein the anode has a voltage of at least 400 mV vs. Li / Li + The electrochemical redox potential, The capacity ratio of the anode to the cathode is less than 1, or the area ratio of the anode to the cathode is less than or equal to 1, or both.
2. The electrochemical cell of claim 1, wherein The capacity ratio of the anode to the cathode is 0.5 to 0.99, and The area ratio of the anode to the cathode is equal to 1.
3. The electrochemical cell of claim 1, wherein the electrochemical cell is characterized by a voltage-capacity curve that is unchanged after being punctured by a blunt tip 2 mm diameter stainless steel nail at a rate of 1 cm / sec.
4. The electrochemical cell of claim 1, wherein the electrochemical cell is characterized by unchanged performance after 1000 cycles and subsequent storage at 0 V for 33 months.
5. The electrochemical cell of claim 1, wherein the electrochemical cell is characterized by less than 10% 1OC capacity fade after 1,000 cycles between 2.43 V and 1.33 V at 1OC charge rate and 1OC discharge rate in a 45°C oven without external constraints.
6. The electrochemical cell of claim 1, wherein the electrochemical cell is characterized by delivering more than 30% capacity when discharged to 1.2 V at a rate of 3.3 C at -50°C.
7. The electrochemical cell of claim 1, which is chargeable at a rate of at least 1C at -50°C.
8. The electrochemical cell of any one of claims 1-7, wherein the anode, cathode, or both comprise a current collector substrate comprising aluminum.
9. The electrochemical cell of any one of claims 1 to 7, wherein the anode and cathode are in a pouch cell.
10. The electrochemical cell of any one of claims 1-7, wherein the anode electrochemically active material comprises an oxide of Nb, Sn, Sb, Ti, Si, or a combination thereof.
11. The electrochemical cell of claim 10, wherein the anode electrochemically active material comprises an oxide of Nb.
12. The electrochemical cell of claim 10, wherein the anode electrochemically active material comprises an oxide of Ti.
13. The electrochemical cell of claim 12, wherein the oxide of Ti has the formula Li 4+a Ti5O 12+b , where -0.3≤a≤3.3, -0.3≤b≤0.
3.
14. The electrochemical cell of any one of claims 1-7, wherein the anode electrochemically active material has an electrochemical redox potential of 1 volt or more relative to lithium metal.
15. The electrochemical cell of any one of claims 1 to 7, wherein the formula Li 1+x MO 2+y M comprises Ni and one or more metals selected from Mg, Sr, Co, Al, Ca, Cu, Zn, Mn, V, Ba, Zr, Ti, Cr, Fe, Mo, B and any combination thereof.
16. The electrochemical cell of any one of claims 1-7, wherein the cathode electrochemically active material comprises Ni and one or more of Mg, Co, or Al.
17. An electrochemical cell comprising: A cathode comprising a cathode electrochemically active polycrystalline material comprising a Li 1+x MO 2+y , wherein -0.9≤x≤0.3, -0.3≤y≤0.3, and wherein M comprises 80 atomic % or more Ni relative to total M, wherein the cathode electrochemically active material comprises a plurality of crystallites and grain boundaries between the plurality of crystallites, wherein the concentration of cobalt, aluminum, or both is higher in the grain boundaries than in the centers of adjacent crystallites, and wherein the concentration of Al, when present, in the grain boundaries is from 0.01 atomic % to 10 atomic %; Two or more anodes comprising an anode electrochemically active material, wherein the two or more anodes have a relative humidity of at least 400 mV vs. Li / Li + The electrochemical redox potential of wherein the anode and the cathode independently further comprise a binder intermixed with the anode electrochemically active material and the cathode electrochemically active material, respectively; The anode and the cathode each independently further comprise a current collector substrate comprising aluminum, wherein the cathode current collector is coated on both sides with the respective electrochemically active material; Porous polyolefin separator; an electrolyte comprising a lithium salt and a carbonate solvent; wherein the two or more anodes are terminal layers of an electrode stack; and The capacity ratio of the anode to the cathode is less than 1.
18. The electrochemical cell of claim 17, wherein the electrochemical cell is characterized by a voltage-capacity curve that is unchanged after being punctured by a blunt tip 2 mm diameter stainless steel nail at a rate of 1 cm / sec.
19. The electrochemical cell of claim 17, wherein the electrochemical cell is characterized by unchanged performance after 1000 cycles and subsequent storage at 0 V for 33 months.
20. The electrochemical cell of claim 17, wherein the unconstrained electrochemical cell is characterized by less than 10% 1OC capacity fade after 1,000 cycles in a 45°C oven at a 1OC charge rate and a 1OC discharge rate between 2.43 V and 1.33 V.
21. The electrochemical cell of claim 17, wherein the electrochemical cell is characterized by delivering more than 40% capacity when discharged to 1.2 V at a 3.3C rate and charged at a 1C rate at -50°C.
22. The electrochemical cell of any one of claims 17-21, wherein the anode electrochemically active material comprises an oxide of Nb, Sn, Sb, Ti, Si, or a combination thereof.
23. The electrochemical cell of claim 22, wherein the oxide of Ti has the formula Li 4+a Ti5O 12+b , where -0.3≤a≤3.3, -0.3≤b≤0.
3.
24. The electrochemical cell of any one of claims 17-21, wherein the formula Li 1+x MO 2+y M comprises Ni and one or more metals selected from Mg, Sr, Co, Al, Ca, Cu, Zn, Mn, V, Ba, Zr, Ti, Cr, Fe, Mo, B and any combination thereof.
25. The electrochemical cell of any one of claims 17-21, wherein the cathode electrochemically active material comprises Ni and one or more of Mg, Co, or Al.